Représentations des enseignants sur leur métier et acquisition de L2 de la part des apprenants : quels liens peuvent être établis ? - Rebecca Starkey-Perret (Recherches en didactique des langues et des cultures)
This article presents results of a qualitative observation and interview study carried out with 5 English teachers in the French secondary school system. The aim of the study is to determine how the teachers' representations of their jobs affect the pedagogical choices they make and the attitudes they have toward learners. First, the classroom observations will be studied through the lens of current theories of acquisition and of educational psychology. Next, the explanations that the teachers themselves give for their classroom actions and behaviors will be studied, thus enabling us to establish which representations have the most impact on pedagogy and, consequently, on acquisition. Finally, it will be shown, through the study of the email exchanges during the year following the classroom observation, how sharing the results of the observation analysis along with theories of acquisition and educational psychology destabilized the teachers' representations and led them to reconsider their pedagogy. This opens new doors for teacher training and the role of researchers in the secondary school system.